Associations of functional health literacy with socioeconomic and demographic status among Filipinos - Lourdes Marie S. Tejero; Kathryn Lizbeth L. Siongco; Paul Adrian V. Pinlac; Kim Carmela D. Co; Ma. Carmen C. Tolabing (BMC Public Health, 2022)
Abstract Background Health literacy determines an individual’s decision-making process in providing judgment concerning appropriate healthcare. Considering the various purposes of literacy for people, functional health literacy (FHL) was identified as a type of literacy that is measured by the application of literacy skills to health-related materials as a result of health education. The objective of this study was to identify the possible socio-demographic correlates of FHL of Filipinos. Methods A cross-sectional survey was conducted among 2,303 Filipinos aged 15 to 70 years old in 2018–2019 utilizing the National Health Literacy Survey. Functional health literacy was determined using the FHL-5 Test which measured prose, document, and numeracy skills. Descriptive analysis presented socio-demographic characteristics and level of FHL. Log-binomial regression was used to estimate associations of FHL adequacy with socio-demographic characteristics. Results Overall, the study involved 1,997 (86.7%) qualified participants. Most of them demonstrated prose literacy skills and had adequate FHL. Adjusted regression analyses showed that participants with a college-level education (Adjusted prevalence ratio [APR]: 1.43, 95% confidence interval [95% CI] 1.27–1.60), categorized under domestic service occupation (APR 1.19, 95% CI: 1.03–1.37), and those residing in urban areas (APR: 1.14, 95% CI 1.06–1.24) were significantly more prevalent in exhibiting FHL adequacy. In contrast, male participants and individuals aged 60 years or above were less likely to demonstrate FHL adequacy. Conclusions The study presents a baseline assessment of the functional health literacy level, measured using the FHL-5 Test, of adults in the Philippines. Majority of the participants demonstrated FHL adequacy, with relatively higher scores in prose than numeracy literacy. The measurement of FHL adequacy can inform policies on methods of health education and communication, emphasizing the need to stratify the audience based on socio-demographic characteristics and adapt the content and design of informational materials for population-based health educational programs.